An Analysis of the Impact on the Performance of Work Safety and Health Workers (Case Study: Construction One Galaxy) Surabaya Project - Khrisna Putra Sasmana (LPPM NAROTAMA UNIVERSITY, Indonesia, 2019)
Number of work accident in the world is still high .In indonesia total of accident case caused by work years 2011- 2014 the highest in 2013 namely 35.917. The purpose of this research to know the influence of safety and health work of the performance of workers the “One Galaxy Surabaya” project. This research including research quantitative , by using kuisioner a gatherer data , sample used is 100 employees “One The Galaxy Surabaya” project, analysis data using test simple linear regression. Based on 6 spss test, obtained the results of the of the respondents, valid responses it is reliable, scattered normal, data does not happen multikolinierity, does not happen heteroskedastys and there is the influence of between health and occupational safety and. employee performance. There is the influence of health and safety work (X) against employee performance (Y) it is proven with the value of the importance of 0,004 smaller than the probability of 0,05 and known the value of r square 0,662. as much as This value containing the sense that the influence of health and safety work (X) on performance employees (Y) reached 66,2 % while 33,8 % the performance of employees affected by other variables that are not researched health and safety work (K3) have been implemented in an optimal so as to improve the performance of a construction worker“One Galaxy Surabaya” project